Methane production by CO2 hydrogenation reaction with and without solid phase catalysis. (1st December 2017) - Falcinelli, Stefano; Capriccioli, Andrea; Pirani, Fernando; Vecchiocattivi, Franco; Stranges, Stefano; Martì, Carles; Nicoziani, Andrea; Topini, Emanuele; Laganà, Antonio
Graphical abstract: Highlights: A prototype experimental apparatus reusing CO2 to produce CH4 was assembled. Experiments and simulations run to a better understanding of the reaction mechanism. An alternative path to a gas-phase-only process to the reduction of CO2 to CH4 has been outlined. Abstract: Leveraging on the experience gained by designing and assembling a prototype experimental apparatus reusing CO2 to produce methane in a reaction with H2, we are developing an alternative innovative cost effective and contaminant resistant synthetic strategy based on the replacement of the solid phase catalysis with a homogeneous gas phase process going through the forming CO2 2+ molecular dications.